Enhanced removal of per- and polyfluoroalkyl substances in complex matrices by polyDADMAC-coated regenerable granular activated carbon. (1st February 2022) - Ramos, Pia; Singh Kalra, Shashank; Johnson, Nicholas W.; Khor, Chia Miang; Borthakur, Annesh; Cranmer, Brian; Dooley, Gregory; Mohanty, Sanjay K.; Jassby, David; Blotevogel, Jens; Mahendra, Shaily
Abstract: Granular activated carbon (GAC) has been used to remove per- and polyfluoroalkyl substances (PFASs) from industrial or AFFF-impacted waters, but its effectiveness can be low because adsorption of short-chained PFASs is ineffective and its sites are exhausted rapidly by co-contaminants. To increase adsorption of anionic PFASs on GAC by electrostatic attractions, we modified GAC's surface with the cationic polymer poly diallyldimethylammonium chloride (polyDADMAC) and tested its capacity in complex water matrices containing dissolved salts and humic acid. Amending with concentrations of polyDADMAC as low as 0.00025% enhanced GAC's adsorption capacity for PFASs, even in the presence of competing ions. This suggests that electrostatic interactions with polyDADMAC's quaternary ammonium functional groups helped bind organic and inorganic ions as well as the headgroup of short-chain PFASs, allowing more overall PFAS removal by GAC. Evaluating the effect of polymer dose is important because excessive addition can block pores and reduce overall PFAS removal rather than increase it. To decrease the waste associated with this adsorption strategy by making the adsorbent viable for more than one saturation cycle, a regeneration method is proposed which uses low-power ultrasound to enhance the desorption of PFASs from the polyDADMAC-GAC with minimum disruption to the adsorbent's structure. Re-modification with the polymer after sonication resulted in a negligible decrease in the sorbent's capacity over four saturation rounds. These results support consideration of polyDADMAC-modified GAC as an effective regenerable adsorbent for ex-situ concentration step of both short and long-chain PFASs from real waters with high concentrations of competing ions and low PFAS loads. Graphical abstract: Image 1 Highlights: pDADMAC-modified GAC successfully removed short-chained PFASs in complex matrices. Critical dose of pDADMAC to modify GAC is needed to avoid negative surface effects. Excessive pDADMAC can mask GAC's pore entrances, causing lower PFAS removal. pDADMAC mitigates electrostatic competition of high cumulative ion/humic acid load. Ultrasound regenerates pDADMAC-GAC with minimum decrease in adsorption capacity.